Konsepsi Negara Menurut M. Natsir: Tinjauan Dari Perspektif Pemikiran Politik Islam - Amin Suyitno (Intizar, 2015)
This research paper discusses about the perspective of M. Natsir on state conception. He was chosen as a figure in this study since he is well known not only as an initiator of Islamic and state conception but also as a main actor in implementing his ideas. This paper summarizes that Islam and a state has an integrally related symbiosis. Religion needs a state, and vice versa. Based on Natsir, Islam is a complete school that contains not only worship but also some aspects such as the field of state. Thus, the establishment of a state is a blessing. Nevertheless, the state is only an instrument, not an objective. On that basis, a head of a country does not need to be titled as a kholifah, but  a president or the others. The important thing is that his characteristics and obligations are in accordance with Islamic values. Seen from his argument construction in some ways, Natsir follows the ideas of Ibn Taimiyah with regard to the urgency of state inevitability. He is also in line with Ibn Khaldun who compares society with the state. Overall, his perspective is influenced by the political perspectives of not only classical Muslims such as al-Mawardi and al-Ahkam al-Sulthaniyya, but also modern Muslims such as al-Maududi and al-Afgani.